Effect of black tea in diethylnitrosamine-induced esophageal carcinogenesis in mice - Velho,Átila Varela (2008)
PURPOSE: To evaluate the effect of black tea on esophageal carcinogenesis induced by the oral administration of diethylnitrosamine (DEN). METHODS: A population of 120 female mice (Mus musculus, strain CF1) were studied for 160 days. The animals were assigned to two control groups and three treatment groups. The control groups received water or tea throughout the study period, while the three experimental groups received DEN weekly, for three consecutive days, and water, tea, or both, in the other days of the week. On completion of the 160-day period, the animals were killed and their esophagi promptly examined macroscopically and subsequently submitted to histopathology (using the hematoxylin-eosin technique). RESULTS: In the comparative analysis between the treatment groups, tumor incidence (macroscopy) was significantly lower in those animals that received black tea besides the carcinogen. As regards the histopathologic changes, there was a greater number of low grade epithelial lesions in the same groups (p < 0.001). CONCLUSION: The animals that received black tea had a lower incidence of effects related to the carcinogen's action, thus indicating that, in this model, the infusion had a significant chemoprophylactic effect on experimental diethylnitrosamine-induced carcinogenesis.